2011
DOI: 10.5761/atcs.oa.09.01518
|View full text |Cite
|
Sign up to set email alerts
|

Release of Serum S-100.BETA. Protein and Neuron-Specific Enolase after Off-Pump Coronary Artery Bypass Grafting with and without Intracranial and Cervical Artery Stenosis

Abstract: Purpose: The aim of this study was to quantify the amount of brain damage suffered by patients who underwent off-pump coronary artery bypass grafting (OPCAB) in which S-100β protein and neuron-specific enolase were used. Methods: Thirty-four patients undergoing scheduled OPCAB were enrolled in the study. The patients were divided into two groups according to the results of their magnetic resonance angiography (MRA) and cervical ultrasonography: 13 patients had cervical or intracranial arterial stenosis (Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…Considering our findings, S100B protein seems to be more useful as a biochemical marker of POCD than NSE. Although controversy remains, several authors were able to demonstrate a relationship between the degree of cognitive dysfunction and S100B protein, 6,9,10,[29][30][31][32][33] which is consistent with our present findings. Considering that S100B protein is highly brain specific, 28 S100B protein may be a better predictive marker of POCD.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Considering our findings, S100B protein seems to be more useful as a biochemical marker of POCD than NSE. Although controversy remains, several authors were able to demonstrate a relationship between the degree of cognitive dysfunction and S100B protein, 6,9,10,[29][30][31][32][33] which is consistent with our present findings. Considering that S100B protein is highly brain specific, 28 S100B protein may be a better predictive marker of POCD.…”
supporting
confidence: 93%
“…concentration occurring 30 min postoperatively and returning to basal levels within 18 h after surgery. 29 Although previous studies indicated NSE as a reliable biochemical marker of postoperative dysfunction, 5,9,10 our study failed to demonstrate a solid association between serum NSE and POCD, since only a weak association between NSE levels immediately after surgery and TICS scores in the seventh and 180th postoperative day and a small interaction between time and POCD regarding NSE serum levels were found. Nevertheless, S100B protein serum levels were significantly increased postoperatively in patients displaying POCD as compared with patients without cognitive dysfunction 21 and 180 days after surgery.…”
contrasting
confidence: 77%
See 2 more Smart Citations
“…The serum levels of IL‐1β, IL‐6, TNF‐α, CRP, and S‐100β protein were measured using enzyme‐linked immunosorbent assay (Biosource, Camarillo, CA, USA), following the manufactures instructions. Previous study suggested that the release of serum S‐100β protein after coronary artery surgery reaches the peak at 1 h post‐operation and gradually decreased until the normal level at 24 h post‐operation . Thus, in the current study, no time points later than 6 h after surgery were considered.…”
Section: Methodsmentioning
confidence: 98%